Effects of dietary supplementation with microencapsulated Galla chinensis tannins on growth performance, antioxidant capacity, and lipid metabolism of young broiler chickens - Ren, Xiaojie; Yuan, Peng; Niu, Jiaxing; Liu, Yang; Li, Yang; Huang, Libo; Jiang, Shuzhen; Jiao, Ning; Yuan, Xuejun; Li, Junxun; Yang, Weiren (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the impacts of dietary supplementation with Galla chinensis tannins (GCT) on the growth performance, antioxidant capacity, and lipid metabolism of young broilers. Overall, a total of 216 healthy 1 day-old broilers were randomly allocated to CON group and GCT group, and provided with a basal diet or a basal diet added with 300 mg/kg microencapsulated GCT, respectively, in a 21 days trial. Our findings indicated that dietary GCT addition had no significant effects (p > 0.05) on growth performance. However, GCT supplementation led to a significant reduction in the total cholesterol (TC) concentration in the serum and liver (p < 0.05). Furthermore, GCT supplementation significantly increased the ratios of high-density lipoprotein (HDL) to low-density lipoprotein (LDL) and HDL to TC in the serum, in addition to elevating the activities of enzymes related to lipid metabolism in the liver (p < 0.05). Dietary GCT addition also improved the antioxidant capacity of the broilers, as evidenced by a significant decrease in the concentration of malondialdehyde in serum and liver (p < 0.05). Additionally, the GCT group exhibited significantly increased expressions of hepatic genes associated with antioxidant enzymes (HO-1, GPX1, SOD2, SIRT1, CPT-1, and PPARα) (p < 0.05), while the mRNA expression of SREBP-1 was significantly decreased (p < 0.05) compared with the CON group. In conclusion, dietary addition of 300 mg/kg microencapsulated GCT improved the antioxidant status and lipid metabolism of broilers without affecting their growth performance.